Features of the conceptual and categorical apparatus of professional motivation of future teachers of physical culture and sports in institutions of secondary vocational education - Barmin S. A. (Psychological and Pedagogical Support of General, Special and Inclusive Education of Children and Adults, 2024)
The article examines the basic concepts that form the conceptual and categorical apparatus of professional motivation of future teachers of physical culture and sports, provides the author's formulations of the concept of "motivation", describes the basic concepts related to motivation (interest, need, goal, orientation, incentives, motives, values, expectations and regulators of motivation), taking into account the specifics research topics.
Keywords: будущие педагоги; физическая культура; спорт; профессиональная мотивация; professional motivation; educational institutions; future teachers; physical culture and sports; понятийно-категориальный аппарат; учреждения СПО; Conceptual and categorical apparatus